Cardiorespiratory fitness mitigates brain atrophy and cognitive decline in adults at risk for Alzheimer's disease. Issue 1 (12th July 2021) - Dougherty, Ryan J.; Jonaitis, Erin M.; Gaitán, Julian M.; Lose, Sarah R.; Mergen, Brandon M.; Johnson, Sterling C.; Okonkwo, Ozioma C.; Cook, Dane B.
Abstract: Introduction: Cardiorespiratory fitness (CRF) may mitigate Alzheimer's disease (AD) progression. This study examined the longitudinal associations of CRF with brain atrophy and cognitive decline in a late‐middle‐aged cohort of adults at risk for AD. Methods: One hundred ten cognitively unimpaired adults (66% female, mean age at baseline 64.2 ± 5.7 years) completed a baseline graded treadmill exercise test, two brain magnetic resonance imaging scans (over 4.67 ± 1.17 years), and two to three cognitive assessments (over 3.26 ± 1.02 years). Linear mixed effects models examined the longitudinal associations adjusted for covariates. Results: Participants with higher baseline CRF had slower annual decline in total gray matter volume ( P  = .013) and cognitive function ( P  = .048), but not hippocampal volume ( P  = .426). Exploratory analyses suggested these effects may be stronger among apolipoprotein E ε4 carriers. Discussion: CRF is a modifiable physiological attribute that may be targeted during the preclinical phase of AD in effort to delay disease progression, perhaps most effectively among those with genetic risk.